Creative Economy Development of Yogyakarta Government - Bambang Wahyudi; I Wayan Midhio; Surryanto Djoko Waluyo (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2016)
In facing ASEAN Economic Community (AEC), Yogyakarta dealt with low-educated employees; quite high regional development imbalances; problems in industrial estate and airports infrastructure development caused by land acquisition; climate change which disturbs land productivity and sustainability of agriculture; the fact of being not a large industrial base; and DIY communities who are relatively creative. The research using qualitative methods. Data was collected through surveys and interviews to analyze the development of work systems and the structural dimension of batik and pottery sociotechnical creative industries covered aspects of human resources, technology, organization and policy settings. The results showed: (1) Yogyakarta has all kinds of creative industries but only batik and pottery become the mainstay; (2) the central government should provide ease of licensing and protection of trademarks, patents, or copyrights, while local governments should improve the quality of creative industries by conducting training and company coaching.